Avoiding negative outcomes: tracking the mechanisms of avoidance learning in humans during fear conditioning - Delgado, Mauricio R.; Jou, Rita L.; LeDoux, Joe; Phelps, Liz (Frontiers in Behavioral Neuroscience, 2009)
Previous research across species has shown that the amygdala is critical for learning about aversive outcomes, while the striatum is involved in reward-related processing. Less is known, however, about the role of the amygdala and the striatum in learning how to exert control over emotions and avoid negative outcomes. One potential mechanism for active avoidance of stressful situations is postulated to involve amygdala-striatal interactions. The goal of this study was to investigate the physiological and neural correlates underlying avoidance learning in humans. Specifically, we used a classical conditioning paradigm where three different conditioned stimuli (CS) were presented. One stimulus predicted the delivery of a shock upon stimulus offset (CS+), while another predicted no negative consequences (CS-). A third conditioned cue also predicted delivery of a shock, but participants were instructed that upon seeing this stimulus, they could avoid the shock if they chose the correct action (AV +). After successful learning, participants could then easily terminate the shock during subsequent stimulus presentations (AV-). Physiological responses (as measured by SCRs) confirmed a main effect of conditioning, particularly showing higher arousal responses during pre (AV+) compared to post (AV-) learning of an avoidance response. Consistent with animal models, amygdala-striatal interactions were observed to underlie the acquisition of an avoidance response. These results support a mechanism of active coping with conditioned fear that allows for the control over emotional responses such as fears that can become maladaptive and influence our decision-making.